Implementation of Regulation Number 25 in 2009 Concerning the Public Services Toward the Regional Organizations of Gorontalo District - Muten Nuna; Ibrahim Ahmad; Arifin Tumuhulawa; Dikson Junus; Roy Marthen Moonti (Jurnal Ilmiah Al-Syir'ah, 2021)
The research aimed to investigate the effectiveness of Regulation Number 25 in 2009 concerning public service on the organization of the local forces and investigate the hindrance factors of the implementation of Regulation Number 25 in 2009 concerning public service on the regional organizations. It was empirical juridical research employing the interview method. The technique of data analysis applied descriptive analysis. Findings revealed that the public services of Gorontalo District's regional organizations had been implemented based on the procedure operational standard and the provision of Legislation, although it was not effective. It can be seen from community satisfaction with administrative services that still need to be addressed and improved. The hindrance factors of implementing public service regulation were human resources and the availability of facilities and infrastructures. In creating public services appropriately with the Legislation, the government should be entirely done to improve employees' awareness. Society or paying attention to the organization management and adequate human resources and facilities and infrastructures can support the role of government in improving the public services, particularly the regional organizations of Gorontalo District.